Surface critical behavior in Ising magnets: Exact results - Abraham, D; Maciołek, A (American Physical Society, 2006)
An exact derivation of the surface magnetizations of the two phases m1I and m1II coexisitng below the bulk critical temperature for the semi-infinite two-dimensional Ising ferromagnet subject to a surface field is given. The surface critical behavior of the difference m1I-m1II is that of the ordinary transition only in a limit of a weak surface field below the wetting temperature.